P-276 Dietary Gluten Alters the Balance of Proinflammatory and Anti-inflammatory Cytokines in the DSS Induced Colitis Model. (February 2017) - Arnold, Jennifer; Hatic, Haris; Ivanoff, Erin; Sorrell, Mckenzie; Berglind, Jennifer
Abstract : Background: Diet and nutrition concerns of patients with Inflammatory Bowel Disease (IBD) are extremely common. Diet can certainly effect clinical symptoms of these diseases, but its role in the pathogenesis of IBD is still unknown. Methods: In this study, we evaluated the effect of wheat gluten on the cytokine profile in the established dextran sulfate sodium (DSS)-induced colitis model. The severity of colitis in control mice (C57BL6) with gluten-containing standard diet versus C57BL6 mice given the gluten-free (GF) feed (n = 10 in each group) was examined. All mice received the 3% DSS for 5 days. Results: At the end of 5 days, the control mice exhibited greater histological damage as well as more severe clinical symptoms. In addition, the wheat gluten induced differences in cytokine pattern in the colonic mucosal tissue. Specifically, the mice receiving the standard diet had a significantly higher expression of pro-inflammatory interferon-gamma (IFN-g), interleukin-17 (IL-17), and tumor necrosis factor-alpha (TNF-a) as well as a significant decrease in the anti-inflammatory interleukin 10 (IL-10) and transforming growth factor beta (TGF-b) after DSS treatment compared to the GF-DSS mice. Conclusions: These data suggest that gluten may contribute to the pathogenesis of IBD by modifying the cytokine profile and decreasing the inflammatory response in the colonic mucosal environment.